Analysis of HFMD Transmissibility Among the Whole Population and Age Groups in a Large City of China - Li, Peihua; Rui, Jia; Niu, Yan; Xie, Fang; Wang, Yifang; Li, Zhuoyang; Liu, Chan; Yu, Shanshan; Huang, Jiefeng; Luo, Li; Deng, Bin; Liu, Weikang; et al. (Frontiers in Public Health, 2022)
Background: Hand-Foot-and-Mouth-Disease (HFMD) has been widely spread in Asia. However, the dissemination characteristics intergroup and between different age groups are still not clear. In this study, we aim to analyze the differences in the transmissibility of HFMD, in the whole population and among age groups in Shenzhen city, by utilizing mathematical models. Methods: A database that reports HFMD cases in Shenzhen city from 2010 to 2017 was collected. In the first stage, a Susceptive-Infected-Recovered model was built to fit data of Shenzhen city and its districts, and Reff was used to assess transmissibility. In the second stage, a cross-age groups SIR model was constructed to calculate the difference in transmissibility of reported cases among three age groups of EV71 virus: 0-3 years, 3-5 years, and over 5 years which was denoted as age group 1, 2, and 3, respectively. Results: From 2010 to 2017, 345,807 cases of HFMD were reported in Shenzhen city, with peak incidence in spring and autumn in Shenzhen city and most of its districts each year. Analysis of the EV71 incidence data by age group revealed that age group 1 have the highest incidence while age group 3 had the lowest incidence. The R2 of the SIR model Shenzhen city population-wide HFMD fit for each region was greater than 0.5, and P<0.001. Differences in Reff values between regions were judged by using analysis of variance (ANOVA) (F=0.541, P=0.744). SiIiRi-SjIjRj models between age groups had R2 over 0.7, and P<0.001. The Reff values between groups show that the 0-2 years old group had the strongest transmissibility, while the 3-5 years old group had the weakest transmissibility . Intra-group transmissibility was strongest in the 0-2 years age group. Conclusion: The incidence rate of HFMD is high in Shenzhen city. In the data on the incidence of EV71 in each age group, the highest incidence was in the 0-2 years age group, and the lowest incidence was in the over 5 years age group. The differences in weekly incidence rate of EV71 among age groups were statistically significant. Children with the age of 0-2 years had the highest transmissibility.